Patient Satisfaction and Intention to Seek Medical Treatment Abroad: A Hospital Service Management Perspective in Singkawang (International Journal of Economics and Management Research, 2025)
Healthcare is a fundamental aspect in improving the quality of life. Patient satisfaction is an important indicator that reflects the extent to which patients' needs and expectations regarding healthcare services are met during the treatment process. The data collection method used in this study was qualitative in nature, involving interviews and observations of patients' experiences with healthcare services. Findings regarding patient dissatisfaction with service flow, waiting times, and administrative inefficiencies align with the stress theory of patient satisfaction, which states that satisfaction occurs when the service received meets or exceeds patient expectations. When expectations are not met, patients feel dissatisfied and seek alternative services perceived as better. In this context, overseas healthcare services are perceived to provide more detailed, faster, and more organized services, which increases patient interest in seeking such services. The study concludes that healthcare providers should focus on improving service quality by addressing waiting times, service flow, and administrative processes to enhance patient satisfaction. This could reduce the growing trend of patients seeking treatment abroad. The findings suggest that improving patient care from a systemic and administrative perspective is essential for maintaining competitive healthcare services and retaining patients.